Quality Test of Lysozyme Chloride Granules - YAMANAKA, YOU; MURO, CHIKAAKI; SHINKUMA, DENJI; MIZUNO, NOBUYASU; HAMAGUCHI, TSUNEO (Japanese Journal of Hospital Pharmacy, 1982)
The quality of five different brands of lysozyme chloride granules (A to E) was evaluated by the dissolution test (U. S. P. XIX) and several in vitro tests. The activity of lysozyme chloride was proportional to its content, whereas the activity of product B was slightly weaker than that of the other products. All the products met the requirements for the disintegration test of J. P. IX. The dissolution rates of the products A and B reached 100% within 60 minutes in the 1st and 2nd fluids (J. P. IX), and water, but those of the products C and E remained below 70% even after 120 minutes in any solution. The dissolution rate of product D was considerably influenced by the dissolution solutions used.